2019
DOI: 10.1111/iej.13124
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and characteristics of pain and discomfort associated with root filled teeth: a practice‐based study

Abstract: Aim To (i) investigate the frequency and characteristics of pain and discomfort associated with root filled teeth in adult patients regularly attending the Public Dental Service in Örebro County, Sweden; (ii) assess the association between symptoms and clinical and radiographic findings; and (iii) explore the impact of pain and discomfort from root filled teeth on daily life. Methodology Patient records of adult patients (≥20 years) scheduled for routine check‐ups in April 2015 were screened to identify indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
(73 reference statements)
1
21
0
4
Order By: Relevance
“…In a systematic review by Nixdorf et al (2010), the frequency of persistent pain after endodontic procedures was estimated to be 5.3%. In a cross‐sectional study, patients undergoing a routine check‐up at 23 Swedish public dental clinics reported pain or discomfort in 4.9% of root filled teeth (Jonsson Sjögren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review by Nixdorf et al (2010), the frequency of persistent pain after endodontic procedures was estimated to be 5.3%. In a cross‐sectional study, patients undergoing a routine check‐up at 23 Swedish public dental clinics reported pain or discomfort in 4.9% of root filled teeth (Jonsson Sjögren et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have evaluated the frequency of persistent pain from root‐filled teeth treated in general dental practice. Jonsson Sjögren et al (2019) reported similar results: pain or discomfort was registered in 4.9% of the root‐filled teeth ( n = 62). The overall pain intensity was also rated as mild (Numeric Rating Scale, NRS = 2.1).…”
Section: Discussionmentioning
confidence: 67%
“…The diagnosis of percussion pain depends on patients’ subjective feelings when knocking the affected teeth 22 . According to the comparison of the reaction between the affected teeth and the normal teeth, percussion pain can be divided into five grades: percussion pain (–) means the reaction of knocking with proper force is the same as that of normal teeth; percussion pain (±) means discomfort or strange feeling is caused by percussion with appropriate strength; percussion pain (+) represents light pain is caused by heavy knocking; percussion pain (+++) means severe pain is caused by tapping; percussion pain (++) is between (+) and (+++).…”
Section: Methodsmentioning
confidence: 99%